Peripheral Blood Lymphocyte Analysis in Oligo- and Polyarticular Juvenile Idiopathic Arthritis Patients Receiving Methotrexate or Adalimumab Therapy: A Cross-Sectional Study - Nagy, Arnold; Mosdosi, Bernadett; Simon, Diana; Dergez, Timea; Berki, Timea (Frontiers in Pediatrics, 2020)
Juvenile idiopathic arthritis (JIA) is an umbrella term for seven distinct chronic immune-mediated diseases. Disease-modifying anti-rheumatic drugs (DMARD) are used to treat the underlying joint inflammation as well as extra-articular manifestations. Immunosuppression is a considerable side effect of the drugs. The main goal of this study was to investigate the effect of different JIA therapies on leukocyte subpopulations, which play a role in immune-defence. Three study groups were established. The first group consisted of JIA patients treated with methotrexate solely, the second one received a combination of methotrexate (MTX) and adalimumab (ADA). The control group was made up of the patients’ healthy siblings. A total of 63 children were recruited. Fourty-one children with JIA and 22 healthy controls were included in the study. The absolute number of CD3+ T-cells was significantly elevated in patients treated with biological therapy compared to healthy controls (p2=0.017). In contrast, the number of CD56+ natural killer cells was significantly lower in children receiving biological therapy in comparison with healthy donors (p2=0.039). A significant alteration was also demonstrated between patients treated with MTX and MTX/ADA group concerning CD 19+ B-cells (p3=0.042). This is the first study that demonstrates significant alterations in the number of B-cells and T-cells with a relative decrease of NK-cell ratios in JIA patients receiving different DMARD therapy.